United Stated and China – geopolitical grasp (Economic and Political Thought, 2016)
States as an object of study play an important cognitive role, which resultsfrom their roles in international relations. This is particularly true for globalsuperpowers that shape the security environment worldwide. The UnitedStates and China are such entities, which as global superpowers shape internationalrelations in the world in order to safeguard their own interests. Itmust be added that their goals to implement this policy may be convergent orcontradictory. The present work presents the implementation of geopoliticsby the United States, aimed at maintaining a dominant position in the world,including, among others, exercising control over transport routes in criticalareas of the globe. In case of China, the situation is similar. It seeks to securefreedom of action on all continents of the world so as to gain economic andmilitary advantage over its rival. Both superpowers have precisely definedgeopolitical, geo-economic and geostrategic concepts, which they implement.The creation of duty free zones/free trade zones may be an example of aneconomic activity, and strategic concepts adopted by both the United Statesand China – an example of a military action.